Filsafat dan Sejarah Perkembangan Ilmu - Siti Mariyah; Ahmad Syukri; Badarussyamsi Badarussyamsi; Ahmad Fadhil Rizki (Jurnal Filsafat Indonesia, 2021)
Philosophy is a science that is extensive, meaning that it is closely related to our daily lives. In fact, it can be said that philosophy is the driving force of our daily lives as individuals and as collective human beings in the form of a society or nation. Bertrand Russell explained that “between theology and science lies in a no man's land. This area is under attack by both theology and science. This no man's land is called "philosophy". Philosophy is said to be the "matter scientiarum" which is the mother of all sciences. Everyone who wants to learn the meaning of life must know the science of philosophy. Dr. Surajiyo in his book "An Introduction to Philosophy" stated that "philosophizing is nothing but living thinking and thinking deeply about life (living thought and thoughtful living). Philosophy of science is not just a methodology or procedure for writing scientific papers. Philosophy of science is a philosophical reflection of the nature of science that will not recognize a stopping point in reaching the target to be achieved, namely truth and reality. Understanding the philosophy of science means understanding the intricacies of science so that the most basic aspects and joints, to understand the perspective of science, the possibility of its development, and the interrelationships between branches of science with one another It can be concluded that philosophy is a science that studies seriously the nature of the truth of all things. Science is a method of thinking objectively in describing and giving meaning to the real world and has principles to organize and systematize. The indicators of science are: Accumulative, the truth is not absolute, objective. There are six phases of scientific development, including; Pre-Ancient Greece Phase, Ancient Greek Phase, Medieval Age Phase, Renaissance Age phase, Modern era phase, and the last Contemporary Age phase